IMPLEMENTASI ACCURATE ONLINE DALAM MEMPERMUDAH PENGELOLAAN LAPORAN KEUANGAN PADA PT. XYZ AKUNTING - Tezar, Muhammad (LPPM Universitas Bina Bangsa, 2024)
The aim of this research is to introduce Accurate Accounting in simplifying the process of creating and managing financial reports, especially for PT. XYZ Accounting. The research method used is a qualitative approach with literature study methods and experimental methods. The research results show that Accurate Accounting provides convenience in terms of use and efficiency in creating and managing financial reports required by companies, one of which is PT. XYZ Akunting, from the Accurate Online data above, it can be seen that PT. XYZ Akunting has a BCA Cash balance (which has been reduced by several charges) of Rp. 98,400,000, with trade receivables of Rp. 2,000,000. Meanwhile, the inventory owned is IDR. 11,750,000 which consists of 10 rolls of cotton cloth, so the total assets recorded are Rp. 112,150,000,-. Meanwhile, on the Liability Side of PT. XYZ Accounting has Accounts Payable of Rp. 11,750,000,-. As for Liabilities, it is IDR. 100,400,000